1995
DOI: 10.1007/bf00400603
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of symptomatic diabetic peripheral neuropathy with the anti-oxidant ?-lipoic acid

Abstract: Anti-oxidant treatment has been shown to prevent nerve dysfunction in experimental diabetes mellitus, thus providing a rationale of potential therapeutic value for diabetic patients. The effects of the anti-oxidant alpha-lipoic acid (thioctic acid) were studied in a 3-week multicentre, randomized, double-blind placebo-controlled trial (Alpha-Lipoic Acid in Diabetic Neuropathy; ALADIN) in 328 non-insulin-dependent diabetic patients with symptomatic peripheral neuropathy who were randomly assigned to treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
256
0
33

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 489 publications
(295 citation statements)
references
References 45 publications
6
256
0
33
Order By: Relevance
“…Shown is a blot representing five independent experiments Lipoic acid has been shown to exert beneficial effects in diabetes-related conditions in which oxidative stress was suggested to have a pathogenic role. The ALADIN study found a beneficial clinical effect of LA in the treatment of diabetic polyneuropathy [30]. In accordance with this, using animal models LA has been shown to prevent the diabetes-related reduction in peripheral nerve conduction velocity and endoneural blood flow [31,32].…”
Section: Discussionmentioning
confidence: 67%
“…Shown is a blot representing five independent experiments Lipoic acid has been shown to exert beneficial effects in diabetes-related conditions in which oxidative stress was suggested to have a pathogenic role. The ALADIN study found a beneficial clinical effect of LA in the treatment of diabetic polyneuropathy [30]. In accordance with this, using animal models LA has been shown to prevent the diabetes-related reduction in peripheral nerve conduction velocity and endoneural blood flow [31,32].…”
Section: Discussionmentioning
confidence: 67%
“…13) There are many reports demonstrating the improvement of endothelial dysfunction in diabetic patients in a dose-dependent manner. Lipoic acid supplementation has been reported to increase the unbound lipoic acid level, which can act as a potent antioxidant and reduce oxidative stress; 27) it is commonly marketed as an adjunct for the treatment of diabetic neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] In many studies, ALA treatment has been shown to improve diabetic-induced endothelial dysfunction, probably due to the antioxidant effect of ALA. 13) 14) However, the effect of ALA treatment in patients with hypertension associated endothelial dysfunction is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The ALADIN and SID-NEY clinical trials of LA showed that its oral or intravenous administration improves nerve conduction velocity and neuropathic symptoms, such as pain, burning, paresthesia, and numbness (42)(43)(44)(45). To date, the therapeutic use of LA in the treatment of diabetic polyneuropathies remains the best documented and the most significant benefit of LA to human health.…”
Section: Clinical Applications Of Lamentioning
confidence: 99%